Niilismo e superação no pensamento de Friedrich Nietzsche - Albuquerque, Selma Regina Nóbrega de (2007)
In the presented dissertation is approached the Niilism theme on Nietzsche’s thought, including its overcoming matter. Firstly, to deal how to know what could be the historical influences that could Nietzsche had suffered in order to understand his own speech about the theme. To deal then the main concepts related to the Niilism theme, which highlights “The Death of God” and its relation to modernity, the meaning of the event in direction to the Niilism overcoming. Facing the polemic related to the fact of considering or not the Nietzscheism overcoming of Niilism opted to investigate what Nietzsche described as world’s adjustment attempts without need of god. These attempts would be always useless and sabotaged, including to all modernity, period that would however, the moment of the most effective rupture relating to old ideals. To give an account the investigation of possibilities and effectuation of superman, the one who would be the bearer of the new way of living and thinking.